Obesity Is Associated with Increased Red Blood Cell Folate Despite Lower Dietary Intakes and Serum Concentrations. Issue 1 (12th November 2014) - Bird, Julia K; Ronnenberg, Alayne G; Choi, Sang-Woon; Du, Fangling; Mason, Joel B; Liu, Zhenhua
Abstract: Background: Folates are essential cofactors in metabolic pathways that facilitate biological methylation and nucleotide synthesis, and therefore have widespread effects on health and diseases. Although obesity is prevalent worldwide, few studies have investigated how obesity interacts with folate status. Objective: Based on data from the NHANES, this study aims to examine the association between body mass index (BMI) and obesity-related metabolic factors with blood folate status. Methods: A nationally representative sample of 3767 adults from the NHANES (2003–2006) was used as the study population. Regression analyses, with and without adjustment for demographic factors and dietary intakes, were performed to examine associations between BMI and metabolic factors with serum and RBC folate. Results: The results indicate serum folate concentrations were lower in obese groups compared to the desirable BMI and overweight categories, paralleling lower intakes in this group. In contrast, RBC folate increased incrementally with BMI. Regression analyses demonstrated an inverse relation between BMI and serum folate but a positive relation for RBC folate ( P < 0.01). Waist circumference, serum triglycerides, and fasting plasma glucose each displayed significant positive relations with RBC folate ( P < 0.01), although relations with serum folate were not significant and consistent. Conclusions: In summary, obesity is associated with decreased serum folate, which parallels decreased folate intakes. In contrast, obesity is positively associated with RBC folate. Therefore, RBC folate, in addition to serum folate, should also be considered as a critical biomarker for folate status, especially in the obese population. Future research is needed to understand how obesity differentially alters serum and RBC folate status because they are associated with a variety of medical complications.